Association between Iris Biological Features and Corneal Biomechanics in Myopic Eyes. (18th November 2021) - Fu, Lin; Dai, Qi; Zhu, Pengzhi; Jia, Xu; Bao, Fangjun; Chen, Xiaoyu; Fu, Yana; Lian, Hengli; Yang, Weihua; Ye, Yufeng
Abstract : Purpose . Iris biological features such as surface features and profile characteristics reflected the development of iris stroma and microvessels. Iris vessels and microcirculation are still lack of effective detection methods, and we can directly observe only the iris surface biological characteristics. This cross-sectional study evaluated the association between iris surface biological features and corneal biomechanics in young adults with myopia. Methods . We recruited 152 patients with myopia aged ≥18 years, from the Eye Hospital of Wenzhou Medical University, who had complete Corneal Visualization Scheimpflug Technology (Corvis ST) data and graded iris surface features. Iris surface features included crypts, furrows, and color measured from digital slit lamp images. The biomechanical properties of the cornea were assessed using Corvis ST. Only 1 eye of each participant was randomly selected for analysis. Associations between the iris surface features and corneal biomechanics were analyzed using linear regression models. The grade of iris crypts, furrows, and color and corneal biomechanical parameters measured with Corvis ST was the main outcome measures. Results . The iris crypts were significantly associated with deflection amplitude at the first applanation (A1 DLA, β = 0.001, P = 0.013 ), A1 delta arc length (A1 dArcL) (β = − 0.001, P = 0.01 ), maximum delta arc length (dArcLM) (β = − 0.004, P = 0.03 ), and stiffness at the first applanation (SP-A1) (β = − 2.092, P = 0.016 ). The iris furrows were only associated with integrated radius (β = − 0.212, P = 0.025 ). Iris color was found not related with corneal biomechanical parameters measured via Corvis ST. Conclusions . Iris surface features were associated with corneal biomechanical properties in myopic eyes; more iris crypts were associated with lower corneal stiffness while more extensive furrows were related with higher corneal stiffness. Iris crypts and furrows may provide useful information on corneal biomechanical properties in myopic eyes.